Drug abuse, media influence, urbanization, membership in gang, parental care on juvenile deviant behaviour leading to motorcycle theft - Mohammad Feroz Kamal, 1976- (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah) - Universiti Teknologi Malaysia, 2018